CEO Pay Components and Aggressive Non-GAAP Earnings Disclosure. (July 2023) - Black, Dirk E.; Black, Ervin L.; Christensen, Theodore E.; Gee, Kurt H.
We examine the relation between CEO pay components and aggressive non-GAAP earnings disclosures using CEO pay components as proxies for managers' short- versus long-term focus. Specifically, we explore the extent to which short-term bonus plan payouts and long-term incentive plan payouts are associated with: (1) Managers' propensity to exclude expense items in excess of those excluded by equity analysts; and, (2) The magnitude of those incremental exclusions. We find that long-term incentive plan payouts are negatively associated with the likelihood and magnitude of aggressive non-GAAP exclusions. Our results are consistent with managers reporting non-GAAP information less aggressively when they are more focused on long-term, rather than short-term, value.